Human epididymis protein 4 (HE4) levels inversely correlate with lung function improvement (delta FEV1) in cystic fibrosis patients receiving ivacaftor treatment - Nagy, Béla; Bene, Zsolt; Fejes, Zsolt; Heltshe, Sonya L; Reid, David; Ronan, Nicola J; McCarthy, Yvonne; Smith, Daniel; Nagy, Attila; Joseloff, Elizabeth; Balla, György; Kappelmayer, János; et al. (Journal of cystic fibrosis, 2019)
BACKGROUND: We have recently shown that human epididymis protein 4 (HE4) levels correlate with the severity of cystic fibrosis (CF) lung disease. However, there are no data on how HE4 levels alter in patients receiving CFTR modulating therapy. METHODS: In this retrospective clinical study, 3 independent CF patient cohorts (US-American: 29, Australian: 12 and Irish: 19 cases) were enrolled carrying at least one Class III CFTR CF-causing mutation (p.Gly551Asp) and being treated with CFTR potentiator ivacaftor. Plasma HE4 was measured by immunoassay before treatment (baseline) and 1-6 months after commencement of ivacaftor, and were correlated with FEV1 (% predicted), sweat chloride, C-reactive protein (CRP) and body mass index (BMI). RESULTS: After 1 month of therapy, HE4 levels were significantly lower than at baseline and remained decreased up to 6 months. A significant inverse correlation between absolute and delta values of HE4 and FEV1 (r = -0.5376; P < .001 and r = -0.3285; P < .001), was retrospectively observed in pooled groups, including an independent association of HE4 with FEV1 by multiple regression analysis (β = -0.57, P = .019). Substantial area under the receiver operating characteristic curve (ROC-AUC) value was determined for HE4 when 7% mean change of FEV1 (0.722 [95% CI 0.581-0.863]; P = .029) were used as classifier, especially in the first 2 months of treatment (0.806 [95% CI 0.665-0.947]; P < .001). CONCLUSIONS: This study shows that plasma HE4 levels inversely correlate with lung function improvement in CF patients receiving ivacaftor. Overall, this potential biomarker may be of value for routine clinical and laboratory follow-up of CFTR modulating therapy.
Keywords: mutace; aminofenoly; dospělí; Cystic Fibrosis Transmembrane Conductance Regulator; BMI; chinolony; WAP Four-Disulfide Core Domain Protein 2; pot; Female; Quinolones; dítě; biologické markery; Biomarkers; Adult; HE4; ženské pohlaví; monitorování léčiv; Ivacaftor; cystická fibróza; lidé; Cystic fibrosis; FEV(1); protein CFTR; Mutation; Aminophenols; Chloride Channel Agonists; protein WFDC2; retrospektivní studie; Male; Cystic Fibrosis; aktivátory chloridových kanálů; Drug Monitoring; index tělesné hmotnosti; Sweat; Biomarker; Forced Expiratory Volume; Sweat chloride; Child; Respiratory Function Tests; mužské pohlaví; respirační funkční testy; Body Mass Index; Retrospective Studies; usilovný výdechový objem; Humans